2020
DOI: 10.1038/s41397-020-0162-5
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of CYP2C19-guided antiplatelet therapy in patients with acute coronary syndrome and percutaneous coronary intervention informed by real-world data

Abstract: Current guidelines recommend dual antiplatelet therapy (DAPT) consisting of aspirin and a P2Y12 inhibitors following percutaneous coronary intervention (PCI). CYP2C19 genotype can guide DAPT selection, prescribing ticagrelor or prasugrel for loss-of-function (LOF) allele carriers Nita A. Limdi,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 61 publications
3
30
0
Order By: Relevance
“…Further, emerging data showing frequent reimbursement across multiple payers 26 and cost-effectiveness of genotype testing at the time of PCI support this strategy. 27…”
Section: Discussionmentioning
confidence: 99%
“…Further, emerging data showing frequent reimbursement across multiple payers 26 and cost-effectiveness of genotype testing at the time of PCI support this strategy. 27…”
Section: Discussionmentioning
confidence: 99%
“…We model the alternative treatments that are not known to have a drug–gene relationship with the indicated genes (NOAC and PCSK9 inhibitor), or have a trace of drug–gene relationship but are found to be cost-effective under genotype-guided strategy (ticagrelor). 15 , 20 , 28 , 29 …”
Section: Methodsmentioning
confidence: 99%
“…As indicated previously, the PGx panel test for the study include the following genes: CYP2C19, CYP2C9/VKORC1, and SLCO1B1. 15,20,28,29 The timelines of the three test strategies are illustrated in Fig. 2.…”
Section: Testing Strategiesmentioning
confidence: 99%
“…[ 1 ] A large body of evidence supports this practice, and many studies have found it to be cost effective. [ 2 4 ] CYP2C19 codes for the major enzyme responsible for the activation of clopidogrel. Individuals carrying one or two copies of no function variants in CYP2C19 are known as Intermediate and Poor Metabolizers, respectively (~1/3 of the population).…”
Section: Introductionmentioning
confidence: 99%